Microwave‐Assisted Cycloaddition Reactions - Bougrin, Khalid; Benhida, Rachid (Microwaves in Organic Synthesis, 2012)
Cycloadditions are particularly useful reactions in organic chemistry and constitute the most effective methods for generating carbo‐ and heterocyclic compounds from unsaturated precursors by forming two bonds in a single operation. In this chapter, a selected list of recent and relevant examples of cycloadditions is reviewed, including [3 + 2] (Huisgen and other so‐called click reactions), [4 + 2] and [2 + 2], together with typical examples of miscellaneous cycloadditions. It has been proven that the application of microwave irradiation has a profound influence on the outcome of the cycloaddition reaction. In particular, we describe the microwave effect, reaction media including solvent‐free transformations and separation processes as important subjects in the context of green and more sustainable chemistry. Efficient and sustainable approaches for the synthesis of heterocycles of interest are also reviewed.